2020
DOI: 10.3390/ijms21165840
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes in Angiogenesis and Anti-angiogenic Therapy in Cancers

Abstract: Angiogenesis is the process through which new blood vessels are formed from pre-existing ones. Exosomes are involved in angiogenesis in cancer progression by transporting numerous pro-angiogenic biomolecules like vascular endothelial growth factor (VEGF), matrix metalloproteinases (MMPs), and microRNAs. Exosomes promote angiogenesis by suppressing expression of factor-inhibiting hypoxia-inducible factor 1 (HIF-1). Uptake of tumor-derived exosomes (TEX) by normal endothelial cells activates angiogenic signaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
124
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 186 publications
(128 citation statements)
references
References 209 publications
3
124
0
1
Order By: Relevance
“…Extensive evidence has confirmed that MSC-EXs play a key role in angiogenesis, tumor growth, and metastasis (inva-sion [27]. In the tumor microenvironment, MSC-EXs can enhance intracellular communication and promote angiogenesis [28]. The mechanism for promoting angiogenesis could be enhancing the tube-forming ability of endothelial cells (ECs) via exosomes.…”
Section: Direct and Indirect Effects Of Msc-exs On Tumorsmentioning
confidence: 99%
“…Extensive evidence has confirmed that MSC-EXs play a key role in angiogenesis, tumor growth, and metastasis (inva-sion [27]. In the tumor microenvironment, MSC-EXs can enhance intracellular communication and promote angiogenesis [28]. The mechanism for promoting angiogenesis could be enhancing the tube-forming ability of endothelial cells (ECs) via exosomes.…”
Section: Direct and Indirect Effects Of Msc-exs On Tumorsmentioning
confidence: 99%
“…It was shown, that tumor-derived exosomes (TEX) are responsible for cancer development, metastasis, and progression by suppression of immune cells [ 27 ]. They are involved in angiogenesis in cancer progression by transporting pro-angiogenic biomolecules [ 28 ]. Exosomes have potential clinical applications as biomarkers and drug carriers in anticancer therapy [ 29 , 30 ] and provide strong potential for imaging of cancer cells [ 9 ].…”
Section: Structure and Function Of Exosomesmentioning
confidence: 99%
“…Different studies demonstrate that TEX are involved in inducing or promoting the process of new blood vessel formation during all stages of tumor development [12,27,48]. The analysis of TEX showed that cargo components also include factors that are essential for angiogenic pathways.…”
Section: Glioblastoma Progressionmentioning
confidence: 99%